Structure and reactivity of transition metal clusters - Hermes, A; Alexander Christoph Hermes (2013)
A range of computational and experimental techniques have been applied to the study of four metal cluster systems. Decorated rhodium clusters RhnOm(N2O)+ (n=4−8,m=0−2) have been investigated both experimentally by IR-MPD and computationally using DFT. The effect of cluster size as well as oxygen coverage on the spectroscopy of the N2O bend are analyzed. The infrared-induced decomposition of N2O on RhnO+m is observed on all cluster sizes, with marked differences as a function of size and oxygen coverage, particularly in the case of Rh5(N2O)+. The oxidation of CO was studied on the surface of small platinum cluster cations PtnO+m(n=3−7,m= 2,4) by IR-MPD at 400 – 2100cm−1. Spectroscopically, oxygen is found to be bound both dissociatively and molecularly on the cluster surface, while the CO band is found to red shift in cluster size, and blue shift with oxygen coverage. Oxidation of CO proceeds on all cluster sizes, with a constant branching ratio of 40% : 60% . DFT calculations identified key stationary points and barriers on the Pt4O2CO+ reaction pathway. The one-colour Ta 2 photodissociation is studied by photoionization and VMI in the range 23500 – 24000cm−1 , finding clear evidence of a fragmentation process producing Ta , which is interpreted as fragmentation of cationic Ta+2at the two photon level. A majority of the observed channels produce either atomic (Ta(4F3/2)) or cationic (Ta+(5F1)) ground state. An improved value for the dissociation energy D0(Ta+2) is obtained, in agreement with computational predictions. The anisotropies observed show weak evidence of a perpendicular transition being involved in the photodissociation process. Finally, the photodissociation dynamics of Cu2 are studied by spectroscopy in the range 36000 – 38200cm−1 as well as VMI. Clear evidence for resonant photolysis of Cu2 is obtained, as a result of both direct dissociation of the Cu+2 2Π ion state as well as dissociation of doubly excited Cu2 states, which leads to a determination of dimer dissociation energies. Finally, the production of Cu+2 is interpreted as evidence of photolysis of Cu3, from which a Cu3 dissociation energy is derived.